Elite female athletes' ventilatory compensation to decreased inspired O2 during the Wingate test - Fallon, S.; Belcoe, A.; Shawcross, C.; May, A.; Monteverde, C.; McCann, D. (Research Quarterly for Exercise and Sport, 2015)
Purpose: The purpose of this study was to determine if anaerobic performance as measured by the Wingate is decremented in elite female athletes when fraction of inspired oxygen is decreased from 20.9% to 10%. Method: Nine collegiate female soccer players (Mweight = 63.2 ± 10 kg, Mheight = 164 ± 4.7 cm, Mage = 18.6 ± 0.5 year) performed 1 Wingate test under each condition separated by at least 24 hr. Oxygen consumption was measured breath by breath using a Sensor-Medics metabolic cart. Postexercise blood lactates were measured using the finger-stick method. During normoxic and hypoxic (10% inspired oxygen [O2]) conditions, participants inhaled air from a 300-L weather balloon during the 30-s test. Results: Peak power, minimum power, average power, postexercise blood lactate, preexercise and postexercise blood O2 saturation, and total O2 consumed during exercise and during recovery were not statistically different between conditions. However, the Fatigue Index and peak ventilation were significantly greater during hypoxia than normoxia (35 ± 11% vs. 27 ± 9% & 91.6 ± 14.2 L/min vs. 75.2 ± 11.1 L/min, respectively, p < .05, Cohen's d = - 0.80 and - 1.29, respectively). Ventilation was elevated during hypoxia within 5 s of beginning the Wingate and remained elevated throughout exercise. This increased ventilation was sufficient to maintain oxygen consumption during exercise. Conclusion: Under hypoxic conditions, the ventilatory response to the Wingate test is perhaps more important than aerobic capacity per se in determining whether or not Wingate performance is decremented.